2019
DOI: 10.1590/1982-0224-20180159
|View full text |Cite
|
Sign up to set email alerts
|

Unusual effect of chemical communication on social aggression in juvenile cichlid fish Cichlasoma paranaense (Cichliformes: Cichlidae)

Abstract: Some fish species are socially organized and show a social rank order which is achieved through aggressive interactions. After hierarchy is settled, such species communicate their ranks through several sensorial cues; this communication is adaptive because it reduces detrimental effects from physical contests. Cichlid fish are socially organized and signal their social ranks through visual, acoustic and chemical communication. The response to signaling may vary according to the species and environment; the kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Since chemical cues play a central role in communicating social status and regulating behavioral interactions among fish, water removal can wash out chemical substances and interfere in social rank signaling in highly social cichlids (57). In C. paranaense, water removal does not increase aggressive interactions, in contrast with evidence in P. scalare, suggesting interspecific differences on the aggressive response to chemical signaling in the social hierarchy (58,59). Changes in water temperature can also alter aggressive behavior in a species-specific manner, since a raise in temperature increases aggressive displays in Apistogramma agassizii and Amatitlania nigrofasciata (60,61), but C. paranaense reduces aggression in lower temperatures (62).…”
Section: Social Behaviormentioning
confidence: 99%
“…Since chemical cues play a central role in communicating social status and regulating behavioral interactions among fish, water removal can wash out chemical substances and interfere in social rank signaling in highly social cichlids (57). In C. paranaense, water removal does not increase aggressive interactions, in contrast with evidence in P. scalare, suggesting interspecific differences on the aggressive response to chemical signaling in the social hierarchy (58,59). Changes in water temperature can also alter aggressive behavior in a species-specific manner, since a raise in temperature increases aggressive displays in Apistogramma agassizii and Amatitlania nigrofasciata (60,61), but C. paranaense reduces aggression in lower temperatures (62).…”
Section: Social Behaviormentioning
confidence: 99%
“…Studies in O. niloticus found that aggression of subordinates, but not dominant fish, was higher when their water was renewed compared with not renewed (Gonçalves‐de‐Freitas et al ., 2008). Nonetheless, in another cichlid Cichlasoma paranaense , 50% water replacement led to a reduction in aggression, suggesting the existence of species specificity in the aggressive response to chemical stimuli in the social environment (Gauy et al ., 2019).…”
Section: Chemical Communication Moleculesmentioning
confidence: 99%